Green tea silver nanoparticles improve physiological motor and cognitive function in BALB/c mice during inflammation - Ninsiima, Herbert Izo; Eze, Ejike Daniel; Ssekatawa, Kenneth; Nalugo, Halima; Asekenye, Caroline; Onanyang, David; Munanura, Edson Ireeta; Ariong, Moses; Matama, Kevin; Zirintunda, Gerald; Mbiydzenyuy, Ngala Elvis; Ssempijja, Fred; et al. (Heliyon, 2023)
Information on the basic changes associated with green tea small molecules in acute inflammation is deficient. The purpose of the study was to characterize and establish the effects of green tea silver nanoparticles (AgNPs) following inflammation in BALB/c male mice. In this study, green tea silver nitrate nanoparticles were characterized and the extract were made up to constitute high (100%), medium (10%), and low (1%) concentrations for administration. Acute inflammation was induced in groups I–V of the experimental rodents by injecting 0.5 ml/kg of fresh egg albumin on the subplantar surface of the right hind paw and animals were monitored for 36 h. Group I–III were administered 100%, 10%, 1% green tea nanoparticles extract while group IV was given diclofenac. Group V was the positive control while group VI was the negative control that received the vehicle. Paw edema was measured at a 2 h interval for 3 days, while the pain was assessed by measuring the locomotion activity using the voluntary wheel running and the anxiety-like behavior. Hypersensitivity was measured through the temperature sensation experiment and a non-linear regression analysis was done. Here, synthesized green tea AgNPs registered an absorbance band at 460 nm, phytochemicals due to presence of organic functional groups of O––C––O of oxycarbons, of C––C of a conjugate alkene, C––O of a stretching bond of a secondary alcohol. The silver green tea nanoparticles were spherical, covered by a slimy layer, capped and stable. Green tea AgNPs significantly decreased temperature hypersensitivity in BALB/c male mice and this demonstrated their protective effects. Low concentrations of green tea nanoparticles inhibited edema thus mimicking effects of diclofenac, however, the percentage of inhibition was highest in medium and high silver-tea nanoparticles concentrations demonstration the importance of concentration in therapeutics. Anxiety was lowest in BALB/c male mice treated with high concentrations of silver green tea nanoparticles, and this led to increased locomotory activity in mice. Green tea AgNPs have strong anti-inflammatory effects at high concentrations. Concentrations of green tea AgNPs modulated basic sensory and motor behaviors in BALB/c male mice demonstrating their importance in complementary and integrative medical practice.
Keywords: Small molecules; Uganda tea; The safety of tea; AgNPs; Physiology of nanoparticles; Green tea synthesis; Silver nanoparticles; Antibiotic resistance; Camellia sinensis